Conflict and Coordination: Analysis of the Rule of Law Construction in the Guangdong-Hong Kong-Macao Greater Bay Area: It is based on the New Concept and New Requirements of "One Country, Two Systems" - Li, Wen (International Journal of Social Sciences and Public Administration, 2024)
Under the system of "one country, two systems", the Guangdong-Hong Kong-Macao Greater Bay Area is characterized by "one country, two systems and three legal regions" and is prone to interregional legal conflicts. The so-called inter-regional legal conflict refers to the conflict in the application of law brought by the implementation of relevant social, political and economic activities due to the different legal provisions, which will hinder the high-quality development of economic and social stability. To resolve interregional legal conflicts and realize the coordinated development of the rule of law in Guangdong, Hong Kong and Macao are the key tasks of "one country, two systems" in the new era. The rule of law coordination between Guangdong, Hong Kong and Macao has its policy and economic foundation. Although many achievements have been made in the coordinated development of the rule of law in the Greater Bay Area, it cannot meet the needs of the coordinated and in-depth development of the rule of law in the Guangdong-Hong Kong-Macao Greater Bay Area in the new era. Referring to the path of building a law-based society, the coordination of the rule of law in the Guangdong-Hong Kong-Macao Greater Bay Area mainly involves three links: the construction of the rule of law coordination organization, both the carrot and the stick, the convergence of rules and the construction of the mechanism for resolving disputes.